2020
DOI: 10.7554/elife.55421
|View full text |Cite
|
Sign up to set email alerts
|

Caterpillar-induced rice volatiles provide enemy-free space for the offspring of the brown planthopper

Abstract: Plants typically release large quantities of volatiles in response to herbivory by insects. This benefits the plants by, for instance, attracting the natural enemies of the herbivores. We show that the brown planthopper (BPH) has cleverly turned this around by exploiting herbivore-induced plant volatiles (HIPVs) that provide safe havens for its offspring. BPH females preferentially oviposit on rice plants already infested by the rice striped stem borer (SSB), which are avoided by the egg parasitoid Anagrus nil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 55 publications
2
50
0
Order By: Relevance
“…This is also the case for our study system. We previously showed that BPH preferentially oviposits on SSB-infested rice plants, thereby avoiding the attraction of the egg parasitoid Anagrus nilaparvatae 25 . These various examples confirm that insect herbivores not only can evolve the ability to use volatiles to identify host plants of better nutritional quality, but also plants where their offspring can escape natural enemies 50 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is also the case for our study system. We previously showed that BPH preferentially oviposits on SSB-infested rice plants, thereby avoiding the attraction of the egg parasitoid Anagrus nilaparvatae 25 . These various examples confirm that insect herbivores not only can evolve the ability to use volatiles to identify host plants of better nutritional quality, but also plants where their offspring can escape natural enemies 50 .…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 11, 2021. ; https://doi.org/10.1101/2021.03.10.434708 doi: bioRxiv preprint BPH is a phloem-sucking insect that feeds at the surface on leaf blades and leaf sheaths 25,59 . Hence, there is usually no direct physical interaction between the two species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations